Process Optimization for Biosingeing of 100% Cotton Terry Towel Fabric Using Box–Behnken Design - Aklilu Azanaw; Asnake Ketema (Advances in Materials Science and Engineering)
In the present day, numerous researchers have paid more attention to the dyeing and finishing quality of environmentally friendly textile products in the world because the lack of outstanding products is an alarming problem. Therefore, the purpose of the present study is to treat the fabric with cellulase enzymes to improve the dyeing and finishing quality. The effects of varying chemical concentrations, temperatures, and processing times were examined in the model and different process parameters were optimized in the preparation biosingeing process. The results of the Box–Behnken design were obtained as R2 = 0.7243, 0.9027, and 0.9966 for optimum absorbency, weight loss, and tensile strength, respectively. The treated fabric was analyzed using FTIR to know the unknown functional group and the chemical bonds on the fabric molecule. Testing of physical properties of the treated fabric was done and the result was comparable with other untreated fabrics. The treated fabric performance was studied at 40, 50, and 60 minutes and at temperatures of 30, 55, and 80°C. The experimental investigation has been carried out to determine the effect of biosingeing on different physical parameters, such as the tensile strength of treated cotton fabric (437 N), which was almost similar to that of the untreated fabric (443 N), with almost no significant differences. K/S value for the biosingeing fabric of treated fabric was 17.58, but the that of the untreated fabric was 15.6, which was significantly different. Thus, the enzymatically treated fabric is of good quality because the protruding fiber was removed in biosingeing process. This ecofriendly singeing preparatory process is an alternative process for terry towel fabrics.